PEMBELAJARAN BERBASIS MASALAH DALAM MENINGKATKAN PRESTASI BELAJAR, KEAKTIFAN DAN KERJASAMA SISWA PADA MATA PELAJARAN FISIKA TOPIK RANGKAIAN LISTRIK - Karmelya Karmelya; Niko Sudibjo (JURNAL INOVASI DAN PEMBELAJARAN FISIKA, 2021)
Student learning achievement in the form of cognitive abilities such as grades are one of the references to learning success. In addition, affective learning outcomes such as cooperation and activeness are also important aspects that need to be considered by teachers. This study aimed to analyze the application of problem-based learning in improving learning achievement, activeness, and cooperation in physics subjects. There have been many previous studies that have applied problem-based learning for the development of physics subject modules. In addition, there are several previous studies examining the application of PBM for physics lessons coupled with other additional learning strategies, however, not many have researched PBM only with the classroom action research. This research employed classroom action research (CAR). The research subjects consisted of 16 class X students aged around 15-17 years. The research instrument used tests, interview sheets, and observation sheets. The results of this classroom action research conclude that the application of Problem Based Learning has succeeded in increasing student achievement, activeness and cooperation in physics subjects with the topic of electrical circuits. Therefore, this study provides direct benefits for physics teaching teachers to become a reference for learning methods in order to improve learning and is useful for students in improving their learning outcomes.